PRODUKTIVITAS USAHATANI DAN SISTEM PEMASARAN UMBI TAKA (TACCA LEONTOPETALOIDES) DI KABUPATEN GARUT - Suhartono Suhartono; Eva Fauziyah (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2022)
Taka tuber is a coastal plant type that can be an alternative food source, but its use is still limited until now. This study aims to determine the productivity and marketing system of taka farming on farmer scale. Respondents were chosen deliberately, namely farmers who had or are currently cultivating taka of 16 respondents. Data were analyzed descriptively by calculating farm revenue, cost and income, farm, labour, and capital productivity. The results showed that taka farming in Cikelet District was not yet efficient. Taka farming, which is sold in the form of tuber is not less profitable then selling flour. Sales in the form of flour produce and cultivate without fertilizer has a ratio of income and costs (R/C) of 1.05 (feasible), work productivity (IDR65,217/HOK) is higher than the standard wages of farm labourers in that area (IDR60,000/HOK). It has capital productivity is 5.04% higher than interest on deposits in banks 0.25-4.45% per year. The taka marketing has been running locally with a fairly short marketing channel from farmers directly to flour makers (tubber) or consumers (flour).